Group Cohesiveness and Adolescent Sense of Community at the ‘Aisyiyah Sidoarjo Orphanage: Group Cohesiveness dan Sense of Community Remaja di Panti Asuhan ‘Aisyiyah Sidoarjo - Maryam, Effy Wardati; Affandi, Ghozali Rusyid; Pariontri, Ramon Ananda (Procedia of Social Sciences and Humanities, 2022)
The problem of sense of community in adolescents who are in the Panti Asuhan ‘Aisyiyah Sidoarjo is characterized by a lack of cohesiveness among adolescents in the orphanage, lack of responsibility for the tasks given by caregivers, lazy behavior, lack of concern among residents of the orphanage, and even juvenile delinquency in the orphanage. This study aims to determine the effect of group cohesiveness on the sense of community in adolescents at the Panti Asuhan 'Aisyiyah Sidoarjo. The subjects in this study were adolescents who were in the Panti Asuhan 'Aisyiyah Sidoarjo, totaling 73 adolescents. Research data were collected using the group cohesiveness scale that was developed by researcher based on Forsyth's theory and the sense of community scale developed by researcher based on the theory of McMillan and Chavis.. Analysis of research data Spearman’s correlation analysis techniques. Result showed a relation between group cohesiveness and sense of community, with Spearman's rho correlation coefficient = 0.290; sig = 0.030 < 0.05. The magnitude of the effect is classified as moderate because it has a correlation coefficient of 0.290. The influence of the group cohesiveness variable on the sense of community is 29%.